Straightforward Route to γ-Sultams via Novel Tandem SN/Michael Addition - Klochkova, Anastasiia; Bubyrev, Andrey; Dar’in, Dmitry; Bakulina, Olga; Krasavin, Mikhail; Sokolov, Viktor (Synthesis, 2021)
A novel tandem approach to trisubstituted γ-sultams has been developed involving N-alkylation of methanesulfonanilides with EWG-substituted allyl bromides followed by intramolecular Michael addition. A series of various isothiazolidine 1,1-dioxides have been prepared under mild transition-metal-free conditions in high yields and trans-diastereoselectivity (confirmed by X-ray crystallography). The dependence of reactivity on electronic properties of substrates has been investigated.
Keywords: sultam; isothiazolidine; tandem; nucleophilic substitution; Michael addition; cyclic sulfonamide; allyl bromide; stereoselective